(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article reveals that learners become more sensitive to vocabulary and ideas presented in their first language as well as in the target language and they gain more extensive and varied vocabulary. Learners reach proficiency levels in all four skills of listening, speaking, reading and writing far beyond what is expected in other English programmes for young learners.